N-Acetyl-Aspartate Level is Decreased in the Prefrontal Cortex in Subjects At-Risk for Schizophrenia - Mondino, Marine; Brunelin, Jerome; SAOUD, Mohamed (Frontiers in Psychiatry, 2013)
Reduced N-Acetyl-Aspartate (NAA) levels have been reported in the prefrontal cortex in patients with schizophrenia using proton magnetic resonance spectroscopy. However, it is unclear whether this NAA reduction predates the illness onset and is reported in subjects at-risk for developing schizophrenia (HRS). The aim of this study was to assess NAA levels in the prefrontal cortex in HRS. We hypothesized that HRS displayed lower NAA levels in the prefrontal cortex compared with healthy controls. Studies assessing levels of NAA/Creatine (NAA/Cr) in the prefrontal cortex in HRS were extracted from literature. Meta-analysis tools were used to compute effect sizes of nine selected studies meeting our inclusion criteria (clinical and/or genetic HRS, groups of HRS and healthy controls matched for age and gender, voxel of analysis placed in the prefrontal cortex). HRS exhibited a significant lower NAA/Cr level (2.15 ± 0.29; n = 208) than healthy controls (2.21 ± 0.32; n = 234) in the prefrontal cortex with a medium pooled effect size (Hedges’s g = -0.42; 95% confidence interval: [-0.61; -0.23]; p< 0.0001) corresponding to an average 5.7% of NAA/Cr decrease. Secondary analysis revealed that this reduction was observed in young HRS (< 40 years old) who have not reached the peak age of risk for schizophrenia (-11%, g = -0.82, p < 0.00001) but not in old HRS (> 40 years old) who have already passed the peak age (g = 0.11, p = 0.56), when they are compared with their matched healthy controls. Our findings suggest that the NAA/Cr reduction in the prefrontal cortex reported in patients with schizophrenia is observable only in HRS who have not passed the peak age of risk for schizophrenia. NAA/Cr level in the prefrontal cortex could therefore be considered as a biological vulnerability marker of schizophrenia.